Religious freedom : the contested history of an American ideal - Wenger, Tisa Joy, 1969- (University of North Carolina Press, 2017)
Religious freedom is often presented as a timeless American ideal, appearing fully formed at the founding of the United States. That is simply not so, Tisa Wenger contends in this sweeping and brilliantly argued work. Instead, American ideas about religious freedom were continually reinvented through a vibrant national discourse that cannot be separated from the evolving politics of race and empire.